The mHealth clinical decision-making tools for maternal and perinatal health care in Sub-Saharan Africa: A systematic review - Gaudensia A. Olomi; Rachel Manongi; Charles E. Makasi; Simon Woodworth; Pendo Mlay; Karen Yeates; Nicola West; Jane E. Hirst; Michael J. Mahande; Blandina T. Mmbaga; Lottie G. Cansdale; Ali S. Khashan (PLoS ONE, 2025)
Introduction mobile Health (mHealth) refers to use of mobile wireless technologies for health. The potential for mHealth to enhance healthcare delivery is supported by near-universal availability of mobile phones and their expanding coverage in low- and middle-income countries. This systematic review analyses the available evidence on mHealth clinical decision-making tools in maternal and perinatal health, and whether they lead to improved maternal and perinatal health outcomes in Sub-Saharan Africa (SSA). Methods Eligibility criteria: Studies conducted in SSA describing mHealth tools piloted or used for clinical decision-making in maternal or perinatal healthcare. Exclusion criteria included mHealth tools used outside of maternal and perinatal healthcare, publications lacking sufficient detail (where information couldn’t be obtained through contacting authors), articles where tools were used on a laptop or desktop computer, and articles not published in English. Data sources: PubMed, CINAHL, EMBASE, Global Health, and Web of Science were searched for relevant articles following a predetermined search strategy with no date restrictions. A limited grey literature search was conducted. Risk of bias: We assessed the quality of included studies using the Cochrane Risk of bias 2 tool, Newcastle- Ottawa scale and COREQ. This comprehensive approach ensured a rigorous evaluation of bias and validity in our systematic review. Data extraction and synthesis: Two independent reviewers screened articles and extracted data. Results 1119 records were screened, and 36 articles met the inclusion criteria. Fifteen mHealth tools were identified across 11 SSA countries. Conclusion mHealth tools for clinical decision-making in maternal and perinatal care were found to be feasible, usable, and acceptable. They demonstrated adequate user satisfaction, and some demonstrated improvement of pregnancy outcomes. However, technologies lack scalability, with only one scaled up nationally, and few tools interacted with existing health information systems or had plans for sustainability. This review will help establish best practice for developing and scaling up mHealth clinical decision-making tools, helping to improve maternal and perinatal healthcare in SSA.